2021
DOI: 10.1177/03000605211032788
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopy is a feasible method for resection of deep infiltrating endometriosis, especially in the rectosigmoid area

Abstract: Objective This study aimed to compare outcomes of mini-invasive surgical treatment of endometriosis, especially conventional laparoscopy with robotic-assisted laparoscopy, and to evaluate the quality of life. Methods One hundred three consecutive patients with endometriosis who had surgery from 2014 to 2017 owing to an indication of pain were enrolled in this retrospective study. The majority (n = 77, 75%) of patients underwent conventional laparoscopy and 18 (17%) had robotic-assisted laparoscopy. The quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The latest study suggests that robot-assisted laparoscopy is a possible method of DIE resection [ 134 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The latest study suggests that robot-assisted laparoscopy is a possible method of DIE resection [ 134 ].…”
Section: Treatmentmentioning
confidence: 99%
“…RAL employs 3D technology, facilitating better visualization of the surgical site and instrumentation with seven degrees of freedom, providing reduced manipulation of tremors, and reducing work fatigue. Likewise, it shortens the learning curve compared with laparoscopic surgery [ 17 , 23 , 24 ]. Results in the intraoperative and postoperative outcomes between RAL and CL are contradictory and questionable in relation to the concept of cost–benefit [ 25 ]; however, it has been shown that although RAL implies a 20% higher cost compared with CL, the benefit is greater in cases of deep endometriosis, especially in implants in the colon and rectum [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we evaluated patients with ENZIAN classification grades 1 to 3, which indicates deep endometriosis, unlike many reports carried out in the United States and European countries that used the American Society for Reproductive Medicine classification (rASRM score) [ 24 , 26 , 27 , 28 ]. In this sense, Keckstein and Hudelist proposed that the rASRM score has greater clinical acceptance and is more useful in cases of infertility secondary to endometriosis, while the ENZIAN classification has greater usefulness in deep endometriosis and a greater relationship with complication rates [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some articles, more radical procedures (e.g., endometriosis surgery with concomitant hysterectomy) were performed and patients with more advanced endometriosis were operated on with RAL according to the revised American Society for Reproductive Medicine (rASRM) staging. This might indicate that the surgeon favored a robotic approach and might have added bias to the results, contributing to differences in operating times [ 24 , 31 ]. However, we did not find significant differences in rASM classification between the two approaches.…”
Section: Discussionmentioning
confidence: 99%